Designing Energy Saving Home Lights Using Microcontroller Based Solar Panels: Designing Energy Saving Home Lights Using Microcontroller Based Solar Panels - Muhammad Syahputra Novelan; Adli Abdillah Nababan (Institute of Computer Science (IOCS), 2020)
As the population increases, the supply of electricity to homes increases and often there is a lack of electricity in supplying electricity to the community With the design and implementation of energy saving lamps using microcontroller-based solar panels is an alternative source for electricity supply at home Energy-saving lighting devices using a microcontroller-based solar panel is a series of devices consisting of solar panels as converters of sunlight into electrical energy then flowed to the Lead Acid battery as a place to store electrical energy, the battery is used to turn on the LED The circuit works when the LDR has detected sunlight then the panel will charge the battery, and if the weather is gloomy the lights will turn on automatically. The energy saving lamps are PLN's electricity savings and help in reducing the electricity costs of PLN in the house, which works automatically By utilizing solar energy to turn on the lights, so that it can be used for home lighting at night